Latitudinal Dependence of the Kelvin‐Helmholtz Instability and Beta Dependence of Vortex‐Induced High‐Guide Field Magnetic Reconnection. Issue 5 (29th April 2020) - Vernisse, Y.; Lavraud, B.; Faganello, M.; Fadanelli, S.; Sisti, M.; Califano, F.; Eriksson, S.; Gershman, D. J.; Dorelli, J.; Pollock, C.; Giles, B.; Avanov, L.; et al.
Abstract: We investigate both large‐ and small‐scale properties of a Kelvin‐Helmholtz (KH) event at the dusk flank magnetopause using Magnetospheric Multiscale observations on 8 September 2015. We first use two types of 3‐D simulations (global and local) to demonstrate that Magnetospheric Multiscale is close to the most KH unstable region, and so the occurrence of vortex‐induced reconnection may be expected. Because they produce low‐shear current sheets, KH vortices constitute a perfect laboratory to investigate magnetic reconnection with large guide field and low asymmetry. Recent works suggest that magnetic reconnection may be suppressed when a current sheet combines large guide field and pressure gradient (which induces a diamagnetic drift). We thus perform a statistical analysis of high‐resolution data for the 69 KH‐induced low‐shear magnetic reconnection events observed on that day. We find that the suppression mechanism is not at work for most of the observed reconnecting current sheets, as predicted, but we also find that almost all nonreconnecting current sheets should be reconnecting according to this model. This confirms the fact that the model provides a necessary but not sufficient condition for reconnection to occur. Finally, based on the same data set, we study the latitudinal distribution of these magnetic reconnection events combined with global magnetospheric modeling. We find that reconnection associated with KH vortices occurs over a significant range of latitudes at the flank magnetopause. It is not confined to the plane where the growth rate is maximum, in agreement with recent 3‐D simulations. Key Points: We use two types of global simulations to locate the KH unstable region at the magnetopause and determine its dynamics We test the diamagnetic‐drift reconnection suppression condition over 69 very low shear current sheets and find an overall agreement We report the broad latitudinal extent of magnetic reconnection locations triggered by KH vortices, consistent with bifluid 3‐D simulations